Helicobacter pylori Eradication in Non-Ulcer Dyspepsia: Clearing up the Controversy - Carlo A Fallone (Canadian Journal of Gastroenterology, 2004)
Veldhuyzen van Zanten et al conducted a double-blind, randomized, multicentre study comparing triple therapy for Helicobacter pylori eradication to placebo for the treatment of nonulcer dyspepsia (NUD) symptoms in adult patients (1). Patients had moderate to severe epigastric pain on entry (rated at least a three on a five-point scale for at least three of the previous 14 days). The main outcome measure was the Mean Dyspepsia Summary Score (MDSS), which represents the mean severity of eight dyspepsia symptoms (epigastric pain, belching, heartburn, upper abdominal bloating, flatulence, sour taste, nausea and halitosis). Of the 1143 patients who were screened for this study in 27 centres across Canada, 157 were randomized. H pylori was eradicated in 82% of the active group compared with 6% in the placebo group. Symptoms improved in both groups over the 12-month study period, but there was no difference between the two groups in MDSS (2.34 in active and 2.30 in placebo groups at baseline, compared with 1.68 and 1.67, respectively, at the last visit). Nor were there differences in any of the individual symptoms, in the proportion of patients who achieved a certain MDSS score or in health care utilization, such as physician visits, need for additional prescriptions or days lost from work. The authors concluded that, compared with placebo, therapy for H pylori produced no sustained improvement of NUD symptoms.